Teaching of differential and integral calculation basics in Lithuanian schools after the teaching reform in mathematics (in 1929–1940) - Kastickaitė, Joana; Banionis, Juozas (Lietuvos matematikos rinkinys, 2010)
The article discusses teaching of differential and integral calculation fundamentals after the reform in the teaching of mathematics (1929–1940) with reference to the textbook of Juozas Stoukus “Basics of Infinite Smallness Analysis” (1925), textbook of Antanas Juška “Basics of Mathematical Analysis” (1934), contemporary curricula of higher schools and articles of mathematicians.
Keywords: differential calculation; integral calculation; function; reform in teaching; applied of differential and integral calculation